2017
DOI: 10.1242/dev.139063
|View full text |Cite
|
Sign up to set email alerts
|

The PAR proteins: from molecular circuits to dynamic self-stabilizing cell polarity

Abstract: PAR proteins constitute a highly conserved network of scaffolding proteins, adaptors and enzymes that form and stabilize cortical asymmetries in response to diverse inputs. They function throughout development and across the metazoa to regulate cell polarity. In recent years, traditional approaches to identifying and characterizing molecular players and interactions in the PAR network have begun to merge with biophysical, theoretical and computational efforts to understand the network as a pattern-forming bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
148
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(150 citation statements)
references
References 163 publications
(319 reference statements)
2
148
0
Order By: Relevance
“…The cell cortex also contains cell polarity proteins (Goldstein and Macara, 2007;Lang and Munro, 2017;St Johnston and Ahringer, 2010;Tepass, 2012). For example, Par proteins can interact with the plasma membrane through binding to lipids or integral membrane proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The cell cortex also contains cell polarity proteins (Goldstein and Macara, 2007;Lang and Munro, 2017;St Johnston and Ahringer, 2010;Tepass, 2012). For example, Par proteins can interact with the plasma membrane through binding to lipids or integral membrane proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The core Par-complex consists of Par6, Par3, and typical protein kinase C (aPKC) (Kemphues et al , 1988; Tabuse et al , 1998). Domain structures of these components and their interactions have been extensively studied(Lang & Munro, 2017). Par3 exhibits membrane binding affinity through its C-terminal domain and the ability to self-oligomerize via its N-terminal CR1 domain, which is essential for its localization and function(Benton, 2003; Mizuno et al , 2003; Krahn et al , 2010; Harris, 2017) Structural studies have revealed that the CR1 domain forms helical polymers of 10 nm diameter(Zhang et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The asymmetric localization of the Par/aPKC complex has been used as an indicator of apical-basal cell polarity in a set of animals, including bilaterians 4,5,14,15,53,56-59,63,66,68,69,76-80 and a cnidaria 5,21 . While in the studied bilaterians this asymmetry is established and maintained since the earliest stages of development 60,63,65,71,88,89 , in the cnidarian N. vectensis there is no early asymmetrical localization of any of the Par components 5,21 and embryonic polarity is controlled by the Wnt signaling system 16,73,[90][91][92] . In spite of these differences, once epithelial tissues form and true-epithelial cell-polarity is established in both bilaterian and cnidarian species, the asymmetric localization of Par proteins become highly polarized and is maintained through development.…”
Section: Par Protein Asymmetry Is Established Early But Not Maintainementioning
confidence: 99%
“…This mechanism is deployed in metazoan cells to establish embryonic and epithelial cell polarity during early development and is critical for axial organization 5,15,17,21,22,36,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] . In most bilaterian cells, symmetry breaking is mediated by the Par system set up maternally during the earliest cleavage stages 5,60,70,71 .…”
Section: Introductionmentioning
confidence: 99%